2021
DOI: 10.1111/bjh.17161
|View full text |Cite
|
Sign up to set email alerts
|

CKLF and IL1B transcript levels at diagnosis are predictive of relapse in children with pre‐B‐cell acute lymphoblastic leukaemia

Abstract: Summary Disease relapse is the greatest cause of treatment failure in paediatric B‐cell acute lymphoblastic leukaemia (B‐ALL). Current risk stratifications fail to capture all patients at risk of relapse. Herein, we used a machine‐learning approach to identify B‐ALL blast‐secreted factors that are associated with poor survival outcomes. Using this approach, we identified a two‐gene expression signature (CKLF and IL1B) that allowed identification of high‐risk patients at diagnosis. This two‐gene expression sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Several recent studies on AML-related diseases have also demonstrated the effectiveness of applying state-of-the-art ML techniques in pattern recognition, risk prediction, and survival prediction. These diseases include acute lymphoblastic leukemia (Fitter et al, 2021 ), myelodysplastic syndrome (Radhachandran et al, 2021 ), breast cancer (Kate and Nadig, 2017 ), prostate cancer (Zolbanin et al, 2015 ; Rabaan et al, 2022 ), rectal cancer (Wang et al, 2022 ), skin cancer (Ahmed et al, 2022 ), nasopharynx cancer (Jing et al, 2020 ), pancreatic cancer (Walczak and Velanovich, 2018 ; Muhammad et al, 2019 ; Wang et al, 2020 ), infective endocarditis (Ris et al, 2019 ), AML in pediatric patients (Hoch et al, 2021 ), and AML with myelodysplasia-related changes (Yu et al, 2021 ). The success observed indicates that contemporary ML techniques can automatically uncover meaningful patterns within vast datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Several recent studies on AML-related diseases have also demonstrated the effectiveness of applying state-of-the-art ML techniques in pattern recognition, risk prediction, and survival prediction. These diseases include acute lymphoblastic leukemia (Fitter et al, 2021 ), myelodysplastic syndrome (Radhachandran et al, 2021 ), breast cancer (Kate and Nadig, 2017 ), prostate cancer (Zolbanin et al, 2015 ; Rabaan et al, 2022 ), rectal cancer (Wang et al, 2022 ), skin cancer (Ahmed et al, 2022 ), nasopharynx cancer (Jing et al, 2020 ), pancreatic cancer (Walczak and Velanovich, 2018 ; Muhammad et al, 2019 ; Wang et al, 2020 ), infective endocarditis (Ris et al, 2019 ), AML in pediatric patients (Hoch et al, 2021 ), and AML with myelodysplasia-related changes (Yu et al, 2021 ). The success observed indicates that contemporary ML techniques can automatically uncover meaningful patterns within vast datasets.…”
Section: Related Workmentioning
confidence: 99%
“…Regarding IL-1β, its role is still controversial in ALL, with a 40-fold increase in IL1B gene expression being observed in B-ALL blasts cultured with hematopoietic growth factors [34] and in MSCs from patients at diagnosis [66]; however, its low expression is associated with a lower overall survival (OS) rate and event-free survival (EFS), and it is considered a predictor of relapse [67]. The IL1B gene is highly polymorphic, and several single-nucleotide variations (SNV) have been associated with increased or decreased secretion of the cytokine IL-1β [68], which is a possible cause for the difference in expression in populations due to ethnic/geographic variations.…”
Section: The Role Of Inflammasomes In Leukemiasmentioning
confidence: 99%